Pantoea sp. Isolated from Tropical Fresh Water Exhibiting N-Acyl Homoserine Lactone Production - Wen-Si Tan; Nina Yusrina Muhamad Yunos; Pui-Wan Tan; Nur Izzati Mohamad; Tan-Guan-Sheng Adrian; Wai-Fong Yin; Kok-Gan Chan (The Scientific World Journal)
N-Acyl homoserine lactone (AHL) serves as signaling molecule for quorum sensing (QS) in Gram-negative bacteria to regulate various physiological activities including pathogenicity. With the aim of isolating freshwater-borne bacteria that can cause outbreak of disease in plants and portrayed QS properties, environmental water sampling was conducted. Here we report the preliminary screening of AHL production using Chromobacterium violaceum CV026 and Escherichia coli [pSB401] as AHL biosensors. The 16S rDNA gene sequence of isolate M009 showed the highest sequence similarity to Pantoea stewartii S9-116, which is a plant pathogen. The isolated Pantoea sp. was confirmed to produce N-3-oxohexanoyl-L-HSL (3-oxo-C6-HSL) through analysis of high resolution mass tandem mass spectrometry.